Respostas

2013-09-10T21:29:34-03:00
X²-5x+6

delta = (-5)²-4.1.6
         = 25- 24 =1


-(-5)+1 =  5+1/ 2 = 6/2 x'=3
  2


-(-5)-1 =  5-1/ 2 = 4/2 x''=2
  2

x²-8+12

delta = (-8)²-4.1.12
        =64-48
        = 16 = 4


-(-8) +4  = 8+4/ 2= 12/2= 6      x'=6
   2 



-(-8) -4  = 8-4/ 2= 4/2= 2     x''=2
   2 


espero ter ajudado

2013-09-11T02:32:44-03:00
 x^{2} -5X - 6 = 0              a=1    b=-5    c= -6
(-b+- \sqrt{b^2-4ac})/2a
delta= \sqrt{(-5)^2 - 4.1.(-6)}
delta= \sqrt{+25 +24}
delta= \sqrt{49}
delta= 7
-(-5) +- 7  .... x'=  +5 + 7  .... x' = 12  ..... x'= 6
   2.1                      2                     2
-(-5) +- 7  .... x''=  +5 - 7  .... x'' = -2  ..... x''= -1
   2.1                        2                   2
S={-1;6}


 x^{2} -8x+12
delta= \sqrt{(-8)^2-4*1*12}
delta= \sqrt{+64-48}
delta= \sqrt{16}
delta=4

 \frac{+8+-4}{2}
x' = 8+4 .... x'=12 .... x'= 6
        2              2 
x'' = 8-4 .... x''= 4 .... x''= 2
        2              2 
S={2;6}